MODEL KNOW-WANT-LEARN DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Abdurrahmansyah Abdurrahmansyah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
The learning of Islamic Religious Education in university classes within PTKI requires innovation and development through a varied model or learning strategy. One of the effective learning models in improving students' skills in understanding the teaching materials is through the K-W-L strategy. This strategy is commonly developed in learning that aims to overcome the difficult problem of understanding the teaching materials that are often used in text learning or script study. The research trials have proved that this model is effective in delivering students' understanding of the learning materials of Islamic Religious Education that are taught.